Hubungan antara Dukungan Teman Sebaya dengan Stres Akademik pada Siswa - Febrianti, Nadya Rizki; Surur, Naharus; Kholili, Ma'rifatin Indah (Universitas Sebelas Maret, 2023)
The objectives of the study are: to describe the level of mutual support, academic stress experienced and analyze the relationship between peer support and academic stress in third class of MIPA SMA Negeri 8 Surakarta. The method used is a quantitative approach with a correlation method. The correlation method was used to determine the relationship between two variables, namely peer support and academic stress. The results of this study show that: (1) The category of collegial support for students in third class of MIPA SMA Negeri 8 Surakarta is at the average level of 44 students (67.7%), (2) category of academic stress in the middle level which is 47 students (72.3%), (3) Pearson Product Moment Correlation test results obtained rcount value of -.302 and rateable value of 0.2441. With these results, it is concluded that the value of rcount is greater than the value of table, so the hypothesis proposed in this study which says